Advances in SARS-CoV-2 receptor-binding domain-based COVID-19 vaccines - Xiaoqing Guan; Yang Yang; Lanying Du (Taylor & Francis Group, 2023)
Introduction The Coronavirus Disease 2019 (COVID-19) pandemic has caused devastating human and economic costs. Vaccination is an important step in controlling the pandemic. Severe acute respiratory coronavirus-2 (SARS-CoV-2), the causative agent of COVID-19, infects cells by binding a cellular receptor through the receptor-binding domain (RBD) within the S1 subunit of the spike (S) protein. Viral entry and membrane fusion are mediated by the S2 subunit. Areas covered SARS-CoV-2 S protein, particularly RBD, serves as an important target for vaccines. Here we review the structure and function of SARS-CoV-2 S protein and its RBD, summarize current COVID-19 vaccines targeting the RBD, and outline potential strategies for improving RBD-based vaccines. Overall, this review provides important information that will facilitate rational design and development of safer and more effective COVID-19 vaccines. Expert opinion The S protein of SARS-CoV-2 harbors numerous mutations, mostly in the RBD, resulting in multiple variant strains. Although many COVID-19 vaccines targeting the RBD of original virus strain (and previous variants) can prevent infection of these strains, their ability against recent dominant variants, particularly Omicron and its offspring, is significantly reduced. Collective efforts are needed to develop effective broad-spectrum vaccines to control current and future variants that have pandemic potential.